1990
DOI: 10.1089/aid.1990.6.805
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Analysis of Dextran Sulfate in Rats as Pertains to Its Clinical Usefulness for Therapy of HIV Infection

Abstract: We administered radiolabeled dextran sulfate (3H labeled on the reducing end, MW approximately 8000) [( 3H]DS) to rats. High-performance liquid chromatography (HPLC) analysis of plasma from animals that were given [3H]DS intravenously revealed an initial plasma half-life of about 30 min. Eleven percent of [3H]DS administered was recovered in the urine in 24 h; this material represented minor breakdown with a molecular weight of 4000 as determined by size exclusion HPLC analysis. When administered orally, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 8 publications
3
30
0
Order By: Relevance
“…DS administered orally to humans is virtually unabsorbed (Lorentsen et al, 1989). From studies in rats it appears that DS is poorly absorbed from the intestinal tUbe and, moreover, it is degraded to small molecules which are no longer active against HlV (Hartman et al, 1990). We considered CD optimal as a drug skeleton because it has a smaller molecular weight than the polysaccharides, and contains a rigid cyclic structure that can be retained in the body without being degraded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DS administered orally to humans is virtually unabsorbed (Lorentsen et al, 1989). From studies in rats it appears that DS is poorly absorbed from the intestinal tUbe and, moreover, it is degraded to small molecules which are no longer active against HlV (Hartman et al, 1990). We considered CD optimal as a drug skeleton because it has a smaller molecular weight than the polysaccharides, and contains a rigid cyclic structure that can be retained in the body without being degraded.…”
Section: Discussionmentioning
confidence: 99%
“…However, a clinical trial with oral OS administration showed no effect in patients with AIDS or ARC (Abrams et el., 1989). Other studies showed that following oral administration to humans or rats, OS is not readily absorbed (Lorentsen et al, 1989;Hartman et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…inefficacy were low absorption rate from the intestine and rapid degradation of the drug in the blood (Lorentsen et al, 1989;Hartman et al, 1990).…”
mentioning
confidence: 99%
“…A dextran sulfate formulation (Mw 8000 KOa) has been investigated in clinical trials in AIOS patients for activity against HIV-1, but was not efficacious when administered orally (Abrams et al, 1989) or intravenously (Flexner et al, 1991). This inactivity is related to the vulnerability of the molecule to metabolism particularly when delivered orally (Hartman et al, 1990). Although heparin is regularly used therapeutically to control blood coagulation, no definitive studies have been reported concerning its antiviral effects in man.…”
Section: Discussionmentioning
confidence: 99%